ANALISIS TINGKAT PENGANGGURAN DI JAWA TENGAH TAHUN 1997-2010 - Ronny Pitartono; Banatul Hayati (Diponegoro Journal of Economics, 2012)
The unemployment rate in Central Java have fluctuated from year to year from 1997 to 2010. The unemployment rate is highest in 2007, reaching 7.70%. While the unemployment rate is the lowest in 2001, amounting to 3.70%. This study aims to analyze the relationship between population, inflation, average - minimum wage districts / cities, and the GDP growth rate with the unemployment rate. The test results showed a correlation coefficient of independent variables that have a positive and significant relationship with the dependent variable is the number of inhabitants and the minimum wage regencies / municipalities in Central Java. Variable numbers of the population has correlation coefficient of 0.755 while the minimum wage variable districts / cities have numbers correlation coefficient of 0.878 so it can be concluded that the higher the population, the greater the minimum wage and district / city positively and significantly associated with the level of unemployment in Central Java. Variable rate of inflation has correlation coefficient of -0.173 points while the variable rate of GDP growth has a correlation coefficient of -0.179 so it can be concluded that the variable inflation rate and GDP growth rate variable has a negative and significant relationship with the level of unemployment in Central Java. Correlation coefficient of inflation rate and GDP growth rate indicated by the negative sign means the rate of inflation and GDP growth rate has no significant relationship with unemployment.